Penerapan Pola Asuh Orangtua pada Remaja Awal di SDN Monggang - Fitriani Mediastuti; Era Revika; Winarsih Winarsih (FORUM ILMIAH KESEHATAN, 2022)
Family is the beginning of a child's life. Parental care is very important for a child's development. The parenting model for children will affect children's development, including in terms of children's social, emotional and intellectual competence. This study aims to determine the model of the application of parenting to children from the child's point of view. This type of research was a survey. The study was conducted at Monggang Elementary School, Pendowoharjo Village, Sewon District, Bantul Regency in 2019. The population in this study was all 5th and 6th graders and the sample was selected using the total population sampling technique. Data analysis was carried out descriptively with the help of the SPSS program. The findings of this study indicate that parents who apply overprotection parenting = 65.9%, emotional warmth = 57.1%, rejection = 68.1% and anxious rearing = 64.8%.Keywords: early adolescence; parent; parentingABSTRAK Keluarga merupakan awal seorang anak mengawali kehidupannya. Pengasuhan orang tua sangat penting untuk perkembangan anak. Model pengasuhan orangtua pada anak akan berpengaruh pada perkembangan anak termasuk dalam hal kompetensi sosial, emosi dan intelektual anak. Penelitian ini bertujuan untuk mengetahui model penerapan pola asuh orangtua terhadap anak yang ditinjau dari sudut pandang anak. Jenis penelitian ini adalah survei. Penelitian dilakukan di SDN Monggang, Desa Pendowoharjo, Kecamatan Sewon, Kabupaten Bantul pada tahun 2019. Populasi dalam penelitian ini seluruh siswa kelas 5 dan 6 dan sampel dipilih dengan teknik total population sampling. Analisis data dilakukan secara deskriptif dengan bantuan program SPSS. Temuan penelitian ini menunjukkan bahwa orang tua yang menerapkan pola asuh overprotection = 65,9%, emotional warmth = 57,1%, rejection = 68,1% dan anxious rearing = 64,8%.Kata kunci: remaja awal; orangtua; pola asuh